Anak-anak dari Tersangka Pembunuhan dan Perlindungan Hak-hak Mereka: Analisis Maqasid al-Shariah dalam Sistem Peradilan Pidana Indonesia - Achmad, Zulkifli; Aisyah (Universitas Islam Negeri Alauddin Makassar, 2026)
This study examines the protection of the rights of children of murder suspects within the Indonesian criminal justice system, an issue that creates a dilemma between the interests of law enforcement and the fulfillment of the rights of children as indirect victims. This study aims to analyze child protection mechanisms within the criminal justice process, evaluate the effectiveness of child protection institutions, and examine the perspective of maqasid al-syariah as a comprehensive framework for solutions. The study employs a qualitative approach using a normative-legal methodology, encompassing case studies, analysis of legal documents, and in-depth interviews with legal practitioners, social workers, and relevant stakeholders. The research findings indicate that Indonesia’s criminal justice system remains suboptimal in protecting children whose parents are suspects in murder cases, as evidenced by weak inter-institutional coordination, limited resources for child support services, and the inadequate application of the best interests of the child principle. From the perspective of maqasid al-syariah, the protection of children is an integral part of hifz al-nafs (protection of life) and hifz al-nasl (protection of lineage), which must be prioritized in legal policy. This study recommends revising regulations to strengthen child protection mechanisms, enhancing the capacity of relevant institutions, developing an integrated support model, and incorporating the values of maqasid al-syariah into child protection policies to establish a fair and child-centered justice system.